نظراتٌ في بلاغة النَّص المناسبة بين خواتيم سورة يونس ومفتتح سورة هود في ضوء نظرية النظم : Some Gazes of Quran Inimitability: The Harmonised between The Epilogues of Surat Yunus and The Beginnings of Surat Hud According to The Theory of Arabic Syntax An-Nazm - Mohamed Shehata (Universitas Ahmad Dahlan, 2022)
This study aims to use a theoretical framework, which is mixed between modern applied linguistics and the theory of Arabic syntax